Kaili Women’s Family Functioning in Central Sulawesi, Indonesia - Jusmiati, Jusmiati; Attamimi, Suraya; Darlis, Darlis; Husain, Muhammad Zakir (UIN Sunan Kudus, 2025)
Although research on family functioning has been widely documented, few studies still examine the important role of women in maintaining family functioning to get through various crises. This paper aims to analyze the efforts of Kaili women in improving family functioning in Central Sulawesi. The study utilizes exploratory case study research design and uses McMaster’s Family Assessment Device (FAD) theory as well as positive psychology analysis. The findings of this study show that the efforts of Kaili women in improving family functioning in Central Sulawesi include six aspects, those are solving problem deliberatively, building interpersonal communication, fostering positive emotions, increasing intimacy, synergizing in the role sharing, and supporting extended family. This empirical research also confirms that both the support of the extended family and the spirit of women as bulonggo (the backbone of the family/ the breadwinner) in the Kaili Tradition are supporting factors for family functioning. In addition, This finding complements McMaster’s family functioning theory, which states that the extended family plays a significant role in family functioning. The theoretical implications of this study will be discussed at the end of this study.